Mechanical design and trajectory planning of a lower limb rehabilitation robot with a variable workspace. (16th May 2018) - Wang, Hongbo; Feng, Yongfei; Yu, Hongnian; Wang, Zhenghui; Vladareanuv, Victor; Du, Yaxin
The early phase of extremity rehabilitation training has high potential impact for stroke patients. However, most of the lower limb rehabilitation robots in hospitals are proposed just suitable for patients at the middle or later recovery stage. This article investigates a new sitting/lying multi-joint lower limb rehabilitation robot. It can be used at all recovery stages, including the initial stage. Based on man–machine engineering and the innovative design for mechanism, the leg length of the lower limb rehabilitation robot is automatically adjusted to fit patients with different heights. The lower limb rehabilitation robot is a typical human–machine system, and the limb safety of the patient is the most important principle to be considered in its design. The hip joint rotation ranges are different in people's sitting and lying postures. Different training postures cannot make the training workspace unique. Besides the leg lengths and joint rotation angles varied with different patients, the idea of variable workspace of the lower limb rehabilitation robot is first proposed. Based on the variable workspace, three trajectory planning methods are developed. In order to verify the trajectory planning methods, an experimental study has been conducted. Theoretical and actual curves of the hip rotation, knee rotation, and leg mechanism end point motion trajectories are obtained for three unimpaired subjects. Most importantly, a clinical trial demonstrated the safety and feasibility of the proposed lower limb rehabilitation robot.